Terror attacks and exchange rates : empirical evidence from developed and emerging countries - Jauhiainen, Oona (2023)
Terrorism and terror attacks form a rising threat to the economy and financial markets, while the research area related to terrorism and foreign exchange markets still remain limited. Investigating terror attacks and exchange rates is essential due to the fundamental position of exchange rates in every international trade. In addition, exchange rates play an important part in pricing international financial instruments, such as derivatives. The aim of this thesis is to investigate the relationship between terrorism and exchange rates from three different viewpoints: geopolitical risk in terms of terrorism and its effect to uncovered interest rate parity (UIP) deviation, cumulative abnormal returns (CAR), and explanatory variables of CAR.